Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Osteoarthritis (Knee, Hand, Hip) - Rakhma Hellmi (Indonesian Rheumatology Associantion, 2023)
Background: Osteoarthritis (OA) is the most common form arthritis in theworld, and its prevalence is predicted to rise higher in the future due toincreasing life expectancy and growing number of elderly population. Withthe emergence of new treatment options in the last several years, a betterunderstanding of OA diagnosis and management is required by everyphysician in Indonesia. Methods: A panel of eight selected rheumatologistsfrom the Indonesian Rheumatologist Association (IRA) developedrecommendations based on key questions formulated by a steeringcommittee from IRA. These recommendation materials were taken fromseveral online databases such as PubMed, Science Direct, and GoogleScholar. Level of evidence and grades of recommendation were thenassigned, and each member of the panelist team will assign a score toexpress their level of agreement. Results: A total of 25 recommendationsdiscussing the diagnosis, pharmacological and non-pharmacologicaltherapies, as well as monitoring for OA were formulated. Conclusion: Theserecommendations can be used to help clinicians in accurately diagnosing OA and choosing the most suitable therapy for their patients. Allrecommendation statements were tailored to the clinical setting, facility, and drug availability in Indonesia.